2019
DOI: 10.2478/fman-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Magnitude of Overhead Costs on the Difference Between ABC and TDABC Systems

Abstract: The objective of this study is to investigate the impact of the magnitude of overhead costs on the results of ABC and TDABC differences. A quantitative research method was used and data were gathered through an extensive literature review. A total of 170 articles that included both ABC and TDABC were found and 37 were used because only 37 articles included both the application of the systems and the comparison of the results of the systems. Correlation analysis and regression analysis were used to test whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…By searching the keywords ''Activity'' and ''Costing'' in the title, and ''ABC'' in the text, they concluded a significant and positive relationship between product diversity and ABC adoption. Likewise, Tarzibashi and Ozyapici (2019) reviewed 37 articles that dealt with the relationship between the number of general costs and the results of implementing ABC and TDABC. These authors concluded that there are differences between both systems: the more indirect costs, the more differences between methods in terms of implementation.…”
Section: Previous Research Reviewing Abcmentioning
confidence: 99%
See 1 more Smart Citation
“…By searching the keywords ''Activity'' and ''Costing'' in the title, and ''ABC'' in the text, they concluded a significant and positive relationship between product diversity and ABC adoption. Likewise, Tarzibashi and Ozyapici (2019) reviewed 37 articles that dealt with the relationship between the number of general costs and the results of implementing ABC and TDABC. These authors concluded that there are differences between both systems: the more indirect costs, the more differences between methods in terms of implementation.…”
Section: Previous Research Reviewing Abcmentioning
confidence: 99%
“…They applied cocitation analysis (co-citation correlation matrix), multivariate statistical techniques: factor analysis, cluster analysis and multidimensional scaling (MDS) considering 61 publications, with 20 or more citations, in academic and professional accounting journals over 11 years . There are some examples of meta-analyses and statistical analyses (Tarzibashi & Ozyapici, 2019;Vargas Alves et al, 2018) applied to previous findings reported by academic research on ABC. Concretely, Alcouffe et al (2019) reviewed 24 documents related to product diversity and ABC's adoption through a metaanalysis (ANOVA, Egger's test).…”
Section: Previous Research Reviewing Abcmentioning
confidence: 99%
“…TDABC is defined as a system that can be quickly adapted to fluctuating conditions and provides more detailed information to decision-makers to obtain administrative and financial results. In addition, the time-oriented activity-based costing system can be considered a tool for developing and improving performance in enterprises (Tarzibashi & Hasan, 2019). The following are the six steps to creating a TDABB model that has been identified: (Ozyürek & Ulutürk, 2016) (1) The TDABC model must be built using the most recent data, (2) It is necessary to calculate the profitability of products, services, and customers, (3) For the company's future development, administrative decisions must be made, (4) It is necessary to calculate the company's production and sales forecasts for the coming The total cost of a variable cost changes in proportion to the degree of total activity or volume of output produced, (2) Fixed Costs: A fixed cost remains unchanged in total for a given period, despite wide changes in the related level of total activity or volume of output produced.…”
Section: -2: Previous Research and What It Distinguishes From The Cur...mentioning
confidence: 99%
“…Many authors [43][44][45] have suggested the combined use of ABC and LCC. However, as has been profusely reported in the literature [46][47][48], it has been very difficult to adopt the traditional ABC model because of the costs incurred during its implementation and maintenance over time [47]. Another disadvantage in applying ABC models in long-term scenarios, is the high level of variability associated with driver behavior [49][50][51][52].…”
Section: Time-driven Activity-based Life-cycle Costingmentioning
confidence: 99%